Sleep Neurophysiology in the Elderly: The Potential of Brain Gym to Improve Quality of Life - Dwirahayu, Yayuk; Mashudi, Sugeng; Irshada, Prima Mulqia (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Sleep disturbances represent a common health problem among older adults due to physiological changes associated with aging, decreased melatonin production, and the presence of chronic diseases. Poor sleep quality has been associated with impaired cognitive function, weakened immune response, increased risk of falls, and reduced overall quality of life. Non-pharmacological interventions such as Brain Gym have been proposed as a potential strategy to improve sleep quality by stimulating the parasympathetic nervous system, enhancing cerebral blood flow, and regulating neurotransmitter activity. This study aimed to examine the effect of Brain Gym on sleep quality among older adults. A quantitative study with a quasi-experimental design using a pretest–posttest control group approach was conducted. The sample consisted of 20 elderly participants selected through purposive sampling based on predetermined inclusion criteria. Brain Gym intervention was administered three times per week for four weeks, with each session lasting 30 minutes. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data were analyzed using the Wilcoxon test to determine differences in sleep quality before and after the intervention. Prior to the intervention, all respondents (100%) were categorized as having poor sleep quality. Following the intervention, eight respondents (80%) demonstrated good sleep quality, while two respondents (20%) remained in the poor category, although their PSQI scores showed improvement. The Wilcoxon test produced a p-value of 0.000 (p < 0.05), indicating a statistically significant difference in sleep quality before and after the intervention. Brain Gym was found to be effective in improving sleep quality among older adults, with an effectiveness rate of 80%. This intervention is simple to implement, safe, and has the potential to be integrated into gerontological nursing care as a non-pharmacological alternative to enhance the quality of life among the elderly.Keywords: brain gym; elderly; neurophysiology; sleep quality; insomnia